Method for producing doped cathode active material

The method of producing cathode active materials by mixing particulate TM oxides with fluoride-containing lithium sources and heat treating them addresses the issues of uneven quality and stability in existing materials, resulting in improved performance for lithium-ion batteries.

JP2025510202APending Publication Date: 2025-04-14BASF SE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024556583
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-25
Filing Date
2023-03-20
Publication Date
2025-04-14

AI Technical Summary

Technical Problem

Existing cathode active materials for lithium-ion batteries suffer from uneven quality, high capacity loss, and poor cycle stability, particularly due to volume changes during charging and discharging.

Method used

A method involving the use of a particulate oxide or (oxy)hydroxide of TM, comprising nickel and manganese with at least 50 mol % manganese, mixed with a fluoride-containing lithium source and optionally additional lithium and dopants, followed by heat treatment at 850-1150°C to produce a cathode active material with improved stability.

Benefits of technology

The method results in cathode active materials with consistent quality, reduced capacity loss, and enhanced cycle stability, effectively addressing the challenges faced by current materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510202000001
    Figure 2025510202000001
  • Figure 2025510202000002
    Figure 2025510202000002
  • Figure 2025510202000003
    Figure 2025510202000003
Patent Text Reader

Abstract

1. A method of making a fluoride-doped cathode active material, the method comprising the steps of: (a) providing a particulate oxide or (oxy)hydroxide or carbonate of TM, the TM comprising nickel and manganese, at least 50 mol % of the TM being manganese, the particulate oxide or (oxy)hydroxide having an average particle size (D50) in the range of 1 to 16 μm; (b) providing a lithium source containing 0.01-2.5 wt. % fluoride, wherein the fluoride is uniformly dispersed within the lithium source; (c) mixing said oxide or (oxy)hydroxide or carbonate of TM with said fluoride-containing lithium source, optionally with an additional lithium source containing less fluoride, and optionally with one or more dopants based on at least one metal other than lithium; (d) heat treating the mixture resulting from step (c); Includes.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a fluoride-doped cathode active material, said method comprising the steps of: (a) providing a particulate oxide or (oxy)hydroxide of TM, the TM being a combination of metals including nickel and manganese, at least 50 mol % of the TM being manganese, the particulate oxide or (oxy)hydroxide having an average particle size (D50) in the range of 1 to 16 μm; (b) providing a lithium source containing 0.01-2.5% by weight of fluoride, the fluoride being uniformly dispersed within the lithium source; (c) mixing said oxide or (oxy)hydroxide of TM with said fluoride-containing lithium source, optionally with an additional lithium source containing less fluoride, and optionally with one or more dopants based on at least one metal other than lithium; (d) heat treating the mixture resulting from step (c); Includes. [Background technology]

[0002] Lithium-ion secondary batteries are modern devices for storing energy. Many applications have been considered, from small devices such as mobile phones and laptop computers to car batteries and other e-mobility batteries. Various battery components such as electrolytes, electrode materials and separators have important roles in the performance of the battery. Cathode materials have received particular attention. Several materials have been proposed, such as lithium iron phosphate, lithium cobalt oxide, and lithium nickel cobalt manganese oxide. Extensive research has been conducted, but the solutions found so far still leave room for improvement.

[0003] Typically, cathode active materials are manufactured using a two-stage process. In the first stage, a sparingly soluble compound of the transition metal(s), such as a carbonate or hydroxide, is prepared by precipitating it from a solution. The sparingly soluble salt is often also called the precursor. In the second stage, the precursor is mixed with a lithium compound, such as Li2CO3, LiOH or Li2O, and calcined at high temperature, such as 600-1100°C. In special recipes, dopants can be added, such as alumina, titania, zirconia, or oxides or (oxy)hydrides of transition metals such as Nb, Ta, W, Mo.

[0004] At present, particular interest is observed in so-called Ni-rich electrode active materials, e.g., electrode active materials containing at least 50 mol % or 75 mol % or more of Ni relative to the total content (where metal refers to metals other than lithium). Some technical questions remain to be resolved. Volumetric energy density, capacity loss, cycling stability are still areas of research and development. Part of the problem is due to the volume change of the cathode active material during charging and discharging. See, for example, US 5,773,168. The method disclosed is to mix a small amount of lithium fluoride with another lithium source, e.g. lithium carbonate, followed by calcination. However, the quality of such materials is often quite heterogeneous. In US 2015 / 0064563, it is proposed to incorporate fluoride by heat treating the cathode active material with a fluorinated polymer, e.g. polyvinylidene difluoride.

[0005] US 2013 / 0209840 discloses a fluoride coating process. The fluoride coating only affects the outer surface of the respective cathode active material. N. Zhang et al., J. Electro-chem. Soc. 2020, 167, 080815, report an experiment on fluoride doping by mixing the precursor with LiOH·H2O and LiF, followed by two-step calcination.

[0006] However, the above materials have been found to vary significantly from sample to sample. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] US 5,773,168 [Patent Document 2] US 2015 / 0064563 [Patent Document 3] US 2013 / 0209840 [Non-patent literature]

[0008] [Non-Patent Document 1] N. Zhang et al., J. Electro-chem. Soc. 2020, 167, 080815 Summary of the Invention [Problem to be solved by the invention]

[0009] It was therefore an object of the present invention to provide a cathode active material with constant quality and improved stability, e.g. lower capacity loss and improved cycling stability. It was further an object of the present invention to provide a method for producing a cathode active material with constant and reproducible quality and improved stability, e.g. lower capacity loss and improved cycling stability. [Means for solving the problem]

[0010] Thus, a method as defined at the beginning has been found, which is also referred to below as the "method of the invention" or "method according to the (present) invention". The method of the invention comprises a sequence of several steps as defined at the beginning, which are also referred to below as step (a), step (b), step (c) etc. In the following, the method of the invention is explained in more detail. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Step (a) comprises providing a particulate oxide or (oxy)hydroxide or carbonate of a combination of metals TM, where the TM comprises nickel and manganese, and where at least 50 mol % of the TM is manganese, said particulate oxide or (oxy)hydroxide having an average particle size (D50) in the range of 1-16 μm, preferably 5-12 μm. The particulate oxide or (oxy)hydroxide or carbonate of TM is also referred to as a "precursor". Preferably, at least 95 mol % of the TM is selected from transition metals, e.g. nickel or manganese. Up to 5 mol %, preferably 1 mol %, of the TM may be Mg or Al. Although the D50 value is strictly a median value, it is often referred to as the average particle size (D50).

[0012] In one embodiment of the invention, the precursor comprises at least one of Mg, Al and Y, or at least one transition metal selected from Ti, Zr, Nb, Ta, Fe, Mo and W. In another embodiment, the precursor contains no metals other than nickel, cobalt and manganese, or no metals other than nickel and manganese.

[0013] In one embodiment of the invention, TM corresponds to the general formula (I): (NiaCobMnc)1-dMd (I) (In the formula, a is in the range of 0.2 to 0.5, preferably 0.3 to 0.4, b is 0 or in the range of 0.01 to 0.1, preferably 0.05 to 0.1, and more preferably 0; c is in the range of 0.5 to 0.8, preferably 0.6 to 0.7; d is in the range of 0 to 0.1, preferably 0.01 to 0.05; M is at least one of Al, Mg, Ti, Mo, Nb, Ta, W, and Zr; a+b+c=1).

[0014] The precursor is preferably obtained by co-precipitation of nickel, cobalt and manganese as hydroxides or carbonates from an aqueous solution containing nitrates, acetates or preferably sulfates of nickel and cobalt and / or manganese in the stoichiometric ratio corresponding to TM. The co-precipitation can be achieved by addition of alkali metal hydroxides or alkali metal carbonates, such as potassium hydroxide or sodium hydroxide, respectively, or potassium carbonate or sodium carbonate, in a continuous, semi-continuous or batch process. After the co-precipitation, the mother liquor is removed, for example by filtration, followed by removal of the water.

[0015] The precursor is particulate. In one embodiment of the present invention, the average particle size (D50) of the precursor is in the range of 1 to 16 μm, preferably 5 to 12 μm, more preferably 7 to 10 μm. The average particle size (D50) in the context of the present invention refers to the median volume-based particle size, which can be determined, for example, by light scattering. In one embodiment, the precursor has a unimodal particle size distribution. In another embodiment, the particle size distribution of the precursor may be bimodal, for example, with one maximum in the range of 1 to 5 μm and a further maximum in the range of 7 to 16 μm.

[0016] The particle shape of the secondary particles of the precursor is spherical, i.e., particles having a spherical shape. Spherical particles include not only particles that are exactly spherical, but also particles whose maximum and minimum diameters differ by 10% or less for at least 90% (number average) of a representative sample.

[0017] In one embodiment of the present invention, the precursor is composed of secondary particles which are agglomerates of primary particles. Preferably, the precursor is composed of spherical secondary particles which are agglomerates of primary particles. Even more preferably, the precursor is composed of spherical secondary particles which are agglomerates of spherical primary particles or platelets.

[0018] In one embodiment of the invention, the precursor has a particle size distribution span in the range of 0.5 to 0.9, the span being defined as [(D90)-(D10)] divided by (D50), all determined by LASER analysis. In another embodiment of the invention, the precursor can have a particle size distribution span in the range of 1.1 to 1.8.

[0019] In one embodiment of the invention, the specific surface (BET) of the precursor, determined by nitrogen adsorption, for example according to DIN-ISO 9277:2003-05, is in the range of 2 to 10 m2 / g, or 10 to 100 m2 / g.

[0020] Some metals are ubiquitous, such as sodium, calcium, or zinc, and trace amounts of them are present virtually everywhere, but such trace amounts are not considered in the context of this invention. Trace amounts of metal in this context means amounts of 0.05 mole % or less based on the total metal content of the TM.

[0021] The precursor may contain a sulfate, e.g., 0.1 to 0.5% by weight of sulfate as determined by ion chromatography.The precursor may contain a carbonate, e.g., 0.1 to 2% by weight of carbonate, each percentage being based on the total weight of the precursor.

[0022] In step (b), a lithium source is provided, wherein the lithium source contains 0.01-2.5 wt. % of fluoride uniformly dispersed within the lithium source. Preferred is 0.05-0.5 wt. %. Percentages are relative to the respective lithium source. The fluoride is preferably lithium fluoride, but may have a counter ion derived from an impurity other than lithium. Preferably, the majority of the fluoride is lithium fluoride. Even more preferably, the fluoride is lithium fluoride.

[0023] The lithium source is selected from lithium carbonate, lithium oxide, Li2O, and lithium hydroxide, LiOH, including but not limited to hydrates of lithium hydroxide, such as LiOH·H2O. Preferred are lithium oxide, Li2O, and lithium hydroxide, LiOH.

[0024] In the lithium source, the fluoride is preferably uniformly distributed as lithium fluoride. The term "uniformly distributed" means that no separate crystals or accumulations of fluoride or LiF are detectable, for example, by X-ray diffraction, particle size distribution, optical microscopy and SEM / EDX (scanning electron microscopy / energy dispersive X-ray spectroscopy). Preference is given to particle size distribution, X-ray diffraction, SEM / EDX.

[0025] Preferably, the fluoride-containing lithium source is produced by recycling used batteries, for example by a recycling process in which lithium carbonate or lithium hydroxide is recovered from a solution of a fluoride-containing lithium salt (e.g. originating from an electrolyte such as LiPF6 or originating from a decomposed fluorine-containing polymer binder).

[0026] In one embodiment of the present invention, the recycling process comprises the following steps: (i) producing black powder (also called black material or active material) by mechanically destroying used lithium ion batteries and then heat treating them; (ii) treating the black powder with at least one of Ca(OH)2 or Mg(OH)2 in the presence of water or a polar solvent other than water at a temperature of at least 70°C, preferably 70 to 120°C; (iii) separating the solid from the liquid, optionally followed by washing the solid residue with a polar solvent such as water, and preferably filtering, thereby obtaining a solution of lithium hydroxide containing fluoride; (iv) optionally after purifying the solution, removing the water from the lithium hydroxide solution in one or more steps, for example by evaporation, to obtain solid LiOH; Includes.

[0027] In another embodiment, steps (i)-(iii) are followed by the step of: (v) adding CO2 or any water soluble carbonate, such as Na2CO3, to precipitate Li2CO3; (vi) Separating the solid from the liquid by solid-liquid separation techniques, for example filtration, optionally followed by washing the solid residue with a polar solvent such as water, thereby obtaining solid fluoride-containing lithium carbonate.

[0028] Lithium hydroxide produced according to the above recycling process usually contains 0.01-1.3% by mass of fluoride relative to the monohydrate of LiOH, preferably 0.05-0.5% by mass. Depending on the drying conditions, anhydrous LiOH is obtained instead of the monohydrate. In this case, the characteristic amounts of the above impurities related to the monohydrate have a higher concentration, respectively, about 1.75 times (corresponding to the molar mass of the monohydrate divided by the molar mass of the anhydrous) relative to 100% anhydrous LiOH.

[0029] Lithium carbonate produced according to the above-mentioned recycling process usually contains 0.01 to 1.5 mass %, and preferably 0.05 to 0.5 mass %, of fluoride.

[0030] Step (c) comprises mixing an oxide or (oxy)hydroxide of TM with said fluoride-containing lithium source, optionally with an additional lithium source containing less fluoride, and optionally with one or more dopants based on at least one metal other than lithium. By carrying out step (c), a mixture is obtained. The expression "said fluoride-containing lithium source" is that provided in step (b). The expression "containing less fluoride" refers in comparison to the lithium source provided in step (b).

[0031] The amount of the total mixture of precursor and lithium source will correspond to the desired stoichiometry of the intended cathode active material. Typically, a stoichiometric amount or a slight excess of lithium relative to the non-lithium metal is selected.

[0032] Step (c) may involve mixing with an additional lithium source that contains less fluoride than the lithium source provided in step (b), for example, 1 to 150 ppm, or below detectable levels.

[0033] The dopants are selected from the oxides, hydroxides and oxyhydroxides of Mg, Ti, Zr, W, Nb, Ta and especially Al. Lithium titanate is a usable titanium source. Examples of dopants include MgO, Mg(OH)2, TiO2 selected from rutile and anatase (preferably anatase), as well as basic titania such as TiO(OH)2, as well as Li4Ti5O12, ZrO2, Zr(OH)4, Li2ZrO3, Nb2O3, Ta2O5, Li2WO4, WO3, MoO3, Li2MoO4, Al(OH)3, Al2O3, Al2O3·aq and AlOOH. Preferred are Al compounds such as Al(OH)3, α-Al2O3, γ-Al2O3, Al2O3·aq and AlOOH, as well as TiO2 and Zr(OH)4. Even more preferred dopants are Al2O3 selected from α-Al2O3, γ-Al2O3, most preferred is γ-Al2O3.

[0034] In a preferred embodiment, the dopant(s) is applied in an amount up to 2.5 mol %, preferably 0.1-1.5 mol %, relative to the TM.

[0035] Examples of suitable equipment for carrying out step (c) include high shear mixers, tumbler mixers, ploughshare mixers and free fall mixers.

[0036] In one embodiment of the present invention, step (c) is carried out at a temperature ranging from room temperature to 200°C, preferably from 20 to 50°C.

[0037] In one embodiment of the invention, step (c) has a duration of 10 minutes to 2 hours. Depending on whether additional mixing is performed in step (d), thorough mixing should be performed in step (c).

[0038] The mixing of the precursor, the lithium source from step (d) and optionally the further lithium source and / or dopant(s) can be carried out all in one step or in sub-steps, for example by first mixing the fluoride-containing lithium source and the dopant(s) and adding such a mixture to the precursor, or by first mixing the precursor and the fluoride-containing lithium source and then adding the dopant and further lithium source, or by first mixing the dopant and the precursor and then adding the fluoride-containing lithium source and further lithium source. Preferably, the precursor and both lithium sources are mixed first, and then the dopant is added.

[0039] In one embodiment of the invention, step (c) comprises the following two substeps: (c1) mixing a fluoride-containing lithium source with a fluoride-free lithium source; and (c2) mixing the mixture resulting from sub-step (c1) with an oxide or (oxy)hydroxide or carbonate of said TM and, where applicable, said dopant(s).

[0040] In one embodiment of the present invention, the mass ratio of the fluoride-containing lithium source to the fluoride-free lithium source provided in step (b) ranges from 20:1 to 1:0, preferably from 1:1 to 1:20.

[0041] In step (c), it is possible to add an organic solvent, such as glycerol or glycol, or water, but it is preferred that step (c) is carried out dry, ie without the addition of water or organic solvents.

[0042] A mixture is obtained.

[0043] Step (d) comprises subjecting said mixture to a heat treatment, for example at a temperature in the range of 850-1150° C., preferably 850-1000° C., more preferably 900-975° C. Heating to 1000-1150° C. is possible, and in such an embodiment, monolith particles are obtained.

[0044] In one embodiment of the present invention, the mixture from step (c) is heated to 850-1000° C. at a heating rate of 0.1-10° C. / min.

[0045] In one embodiment of the present invention, the temperature is increased before reaching the desired temperature of 850° C. to 1150° C., preferably 900° C. to 975° C. or 1000° C. to 1150° C. For example, the mixture from step (c) is first heated to 350° C. to 550° C., then held constant for a time period of 10 minutes to 4 hours, and then increased from 850° C. to 1000° C. or 1150° C.

[0046] In embodiments in which at least one solvent was used in step (c), such solvent(s) may be removed, either as part of step (d) or separately, before starting step (d), for example by filtration, evaporation or distillation of such solvent(s). Evaporation and distillation are preferred.

[0047] In one embodiment of the present invention, step (d) is carried out in a roller hearth kiln, a pusher kiln or a rotary kiln, or a combination of at least two of them. A rotary kiln has the advantage that the homogenization of the material produced therein is very good. In roller hearth kilns and pusher kilns, different reaction conditions for different steps can be set very easily. In laboratory scale experiments, box furnaces, tube furnaces and split tube furnaces can also be used.

[0048] In one embodiment of the present invention, step (d) is carried out in an oxygen-containing atmosphere, such as a nitrogen-air mixture, a noble gas-oxygen mixture, air, oxygen or oxygen-enriched air. In a preferred embodiment, the atmosphere in step (d) is selected from air, oxygen and oxygen-enriched air. The oxygen-enriched air can be, for example, a 50:50 volumetric ratio of air and oxygen. Other options include a 1:2 volumetric ratio of air and oxygen, a 1:3 volumetric ratio of air and oxygen, a 2:1 volumetric ratio of air and oxygen, and a 3:1 volumetric ratio of air and oxygen.

[0049] In one embodiment of the invention, the stoichiometry of lithium in step (c) is in the range of 90-95 mol % relative to the sum of TM and optionally non-lithium metals from the dopant(s), and step (d) is followed by another step of mixing with a lithium source and another heat treatment step.

[0050] By practicing the method of the present invention, cathode active materials are obtained that exhibit excellent stability, such as low capacity loss and high cycling stability.

[0051] Another aspect of the present invention is a cathode active material, hereinafter also referred to as the cathode active material of the present invention. The cathode active material of the present invention is represented by the general formula Li1+xTM1-xO2-yFy and has an average particle size (D50) in the range of 1-16 μm, preferably 1-3 μm, or 5-12 μm, more preferably 7-10 μm. The TM in the cathode active material of the present invention comprises Ni and Mn, where at least 50 mol% of the TM is manganese, x is in the range of 0.05-0.4, preferably 0.2-0.35, y is in the range of 0.0002-0.03, and F is uniformly distributed in such cathode active material. The embodiment with an average particle size of 1-3 μm is preferably a so-called monolithic or single crystal particle.

[0052] F as fluoride is uniformly distributed in the cathode active material of the present invention. That is, F is not accumulated on the outer surface of the secondary particles, but is present inside the secondary particles. Some fluoride may accumulate at the grain boundaries of the primary particles, but preferably does not accumulate there. Furthermore, there are almost no secondary particles that do not contain fluoride.

[0053] The cathode active material of the present invention is particulate. In one embodiment of the present invention, the average particle size (D50) of the cathode active material of the present invention is in the range of 1 to 16 μm, preferably 1 to 3 μm or 5 to 12 μm, more preferably 7 to 10 μm. The average particle size (D50) in the context of the present invention refers to the median particle size on a volume basis, which can be determined, for example, by light scattering. In one embodiment, the precursor has a unimodal particle size distribution. In another embodiment, the particle size distribution of the precursor may be bimodal, for example, with one maximum in the range of 1 to 5 μm and a further maximum in the range of 7 to 16 μm.

[0054] The particle shape of the secondary particles of the cathode active material of the present invention is preferably spherical, i.e., particles having a spherical shape. Spherical particles include not only particles that are exactly spherical, but also particles whose maximum and minimum diameters of at least 90% (number average) of a representative sample differ by no more than 10%.

[0055] In one embodiment of the present invention, the cathode active material of the present invention is composed of secondary particles that are agglomerates of primary particles. Preferably, the precursor is composed of spherical secondary particles that are agglomerates of primary particles. Even more preferably, the precursor is composed of spherical secondary particles that are agglomerates of spherical primary particles or platelets.

[0056] In one embodiment of the invention, the cathode active material of the invention has a particle size distribution span in the range of 0.5 to 0.9, the span being defined as [(D90)-(D10)] divided by (D50), all determined by LASER analysis. In another embodiment of the invention, the precursor can have a particle size distribution span in the range of 1.1 to 1.8.

[0057] In one embodiment of the present invention, the specific surface (BET) of the cathode active material of the present invention, determined by nitrogen adsorption, for example according to DIN-ISO 9277:2003-05, is in the range of 0.1 to 1.5 m2 / g, preferably 0.2 to 1.0 m2 / g.

[0058] In one embodiment of the present invention, the TM in the cathode active material of the present invention is a combination of metals according to general formula (I): (NiaCobMnc)1-dMd (I) (In the formula, a is in the range of 0.2 to 0.5, preferably 0.3 to 0.4, b is 0 or a value in the range of 0.01 to 0.1, preferably 0.05 to 0.1, and more preferably 0; c is in the range of 0.5 to 0.8, preferably 0.6 to 0.7; d is in the range of 0 to 0.1, preferably 0.01 to 0.05; M is at least one of Al, Mg, Ti, Mo, Nb, Ta, W, and Zr; a+b+c=1).

[0059] A further aspect of the present invention relates to electrodes comprising at least one particulate cathode active material according to the present invention. These are particularly useful for lithium-ion batteries. Lithium-ion batteries comprising at least one electrode according to the present invention exhibit good cycling behavior / stability. The electrodes comprising at least one particulate cathode active material according to the present invention are also referred to below as cathodes of the present invention or cathodes of the present invention.

[0060] Specifically, the cathode of the present invention comprises: (A) at least one particulate cathode active material of the present invention; (B) Carbon in a conductive state; (C) Binder material, also called binder (C), and preferably (D) Current collector Contains:

[0061] In a preferred embodiment, the cathode of the present invention comprises, based on the sum of (A), (B) and (C), (A) 80 to 98% by mass of a particulate cathode active material of the present invention; (B) 1 to 17 mass% carbon, (C) 1 to 15 mass % of a binder Contains:

[0062] The cathodes according to the present invention may include additional components. They may include a current collector, such as, but not limited to, aluminum foil. They may further include conductive carbon and a binder.

[0063] The cathode according to the present invention contains a conductively modified carbon, also called carbon (B) for short, which can be selected from soot, activated carbon, carbon nanotubes, graphene, and graphite, and combinations of at least two of the foregoing.

[0064] Suitable binders (C) are preferably selected from organic (co)polymers. Suitable (co)polymers, i.e. homopolymers or copolymers, can be selected, for example, from (co)polymers obtainable by anionic (co)polymerization, catalytic (co)polymerization or free radical (co)polymerization, in particular from polyethylene, polyacrylonitrile, polybutadiene, polystyrene and copolymers of at least two comonomers selected from ethylene, propylene, styrene, (meth)acrylonitrile and 1,3-butadiene. Polypropylene is also suitable. Polyisoprene and polyacrylates are furthermore suitable. Polyacrylonitrile is particularly preferred.

[0065] In the context of the present invention, polyacrylonitrile is understood to mean not only polyacrylonitrile homopolymers but also copolymers of acrylonitrile with 1,3-butadiene or with styrene. Polyacrylonitrile homopolymers are preferred.

[0066] In the context of the present invention, polyethylene is understood to mean not only homopolyethylene, but also copolymers of ethylene with at least 50 mol% copolymerized ethylene and up to 50 mol% of at least one further comonomer, such as α-olefins, such as propylene, butylene (1-butene), 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-pentene, and also isobutene, vinyl aromatics, such as styrene, and also (meth)acrylic acid, vinyl acetate, vinyl propionate, C1-C10-alkyl esters of (meth)acrylic acid, in particular methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, 2-ethylhexyl acrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, and also maleic acid, maleic anhydride and itaconic anhydride.Polyethylene can be HDPE or LDPE.

[0067] In the context of the present invention, polypropylene is understood to mean not only homopolypropylene but also copolymers of propylene with at least 50 mol % copolymerized propylene and up to 50 mol % of at least one further comonomer, such as ethylene, and α-olefins, such as butylene, 1-hexene, 1-octene, 1-decene, 1-dodecene and 1-pentene. The polypropylene is preferably isotactic polypropylene or essentially isotactic polypropylene.

[0068] In the context of the present invention, polystyrene is understood to mean not only homopolymers of styrene, but also copolymers with acrylonitrile, 1,3-butadiene, (meth)acrylic acid, C1-C10-alkyl esters of (meth)acrylic acid, divinylbenzene, in particular 1,3-divinylbenzene, 1,2-diphenylethylene and α-methylstyrene.

[0069] Another preferred binder (C) is polybutadiene.

[0070] Other suitable binders (C) are selected from polyethylene oxide (PEO), cellulose, carboxymethyl cellulose, polyimides and polyvinyl alcohol.

[0071] In one embodiment of the present invention, the binder (C) is chosen from (co)polymers having an average molecular weight MW ranging from 50,000 g / mol to 1,000,000 g / mol, preferably up to 500,000 g / mol.

[0072] The binder (C) may be a crosslinked or non-crosslinked (co)polymer.

[0073] In a particularly preferred embodiment of the present invention, the binder (C) is selected from halogenated (co)polymers, in particular fluorinated (co)polymers.Halogenated or fluorinated (co)polymers are understood to mean (co)polymers that contain at least one (co)polymerized (co)monomer with at least one halogen atom or at least one fluorine atom per molecule, more preferably at least two halogen atoms or at least two fluorine atoms per molecule.Examples include polyvinyl chloride, polyvinylidene chloride, polytetrafluoroethylene, polyvinylidene fluoride (PVdF), tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), vinylidene fluoride-tetrafluoroethylene copolymer, perfluoroalkyl vinyl ether copolymer, ethylene-tetrafluoroethylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, and ethylene-chlorofluoroethylene copolymer.

[0074] Suitable binders (C) are especially polyvinyl alcohol and halogenated (co)polymers such as polyvinyl chloride or polyvinylidene chloride, especially fluorinated (co)polymers such as polyvinyl fluoride and especially polyvinylidene fluoride and polytetrafluoroethylene.

[0075] The cathode of the present invention may include 1 to 15% by weight of binder(s) relative to the cathode active material of the present invention. In other embodiments, the cathode of the present invention may include 0.1% or more and less than 1% by weight of binder(s).

[0076] A further aspect of the invention is a battery containing at least one cathode comprising the cathode active material of the invention, carbon, and a binder, at least one anode, and at least one electrolyte.

[0077] The cathode embodiments of the present invention have already been described in detail above.

[0078] The anode may contain at least one anode active material, such as carbon (graphite), TiO2, lithium titanium oxide, silicon, or tin. The anode may further contain a current collector, such as a metal foil, such as copper foil.

[0079] The electrolyte may include at least one non-aqueous solvent, at least one electrolyte salt, and optionally, additives.

[0080] The non-aqueous solvent for the electrolyte may be liquid or solid at room temperature and is preferably selected from polymers, cyclic or acyclic ethers, cyclic and acyclic acetals, and cyclic or acyclic organic carbonates.

[0081] Examples of suitable polymers are in particular polyalkylene glycols, preferably poly-C1-C4-alkylene glycols and in particular polyethylene glycols, where the polyethylene glycols may contain up to 20 mol % of one or more C1-C4-alkylene glycols. The polyalkylene glycols are preferably polyalkylene glycols with two methyl or ethyl end caps.

[0082] Suitable polyalkylene glycols, especially suitable polyethylene glycols, may have a molecular weight MW of at least 400 g / mol.

[0083] Suitable polyalkylene glycols, in particular suitable polyethylene glycols, may have a molecular weight MW of up to 5 000 000 g / mol, preferably up to 2 000 000 g / mol.

[0084] Examples of suitable acyclic ethers are, for example, diisopropyl ether, di-n-butyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, with 1,2-dimethoxyethane being preferred.

[0085] Examples of suitable cyclic ethers are tetrahydrofuran and 1,4-dioxane.

[0086] Examples of suitable acyclic acetals are, for example, dimethoxymethane, diethoxymethane, 1,1-dimethoxyethane and 1,1-diethoxyethane.

[0087] An example of a suitable cyclic acetal is 1,3-dioxane, and especially 1,3-dioxolane.

[0088] Examples of suitable acyclic organic carbonates are dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.

[0089] Examples of suitable cyclic organic carbonates are compounds according to general formulae (II) and (III) [ka] where R1, R2 and R3 can be the same or different and are selected from hydrogen and C1-C4-alkyl, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl, preferably R2 and R3 are not both tert-butyl.

[0090] In particularly preferred embodiments, R1 is methyl and R2 and R3 are each hydrogen, or R1, R2 and R3 are each hydrogen.

[0091] Another preferred cyclic organic carbonate is vinylene carbonate of formula (IV).

[0092] [ka]

[0093] Preferably, the solvent or solvents are used in an aqueous state, ie with a water content in the range of 1 ppm to 0.1% by weight, which can be determined, for example, by Karl Fischer titration.

[0094] The electrolyte (C) further comprises at least one electrolyte salt. Suitable electrolyte salts are in particular lithium salts. Examples of suitable lithium salts are LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiC(CnF2n+1SO2)3, lithium imides such as LiN(CnF2n+1SO2)2 (wherein n is an integer ranging from 1 to 20), LiN(SO2F)2, Li2SiF6, LiSbF6, LiAlCl4, and salts of the general formula (CnF2n+1SO2)tYLi. where t=1 when Y is selected from oxygen and sulfur; when Y is selected from nitrogen and phosphorus, t=2; When Y is selected from carbon and silicon, t=3).

[0095] Preferred electrolyte salts are selected from LiC(CF3SO2)3, LiN(CF3SO2)2, LiPF6, LiBF4, LiClO4, with LiPF6 and LiN(CF3SO2)2 being particularly preferred.

[0096] In one embodiment of the present invention, the battery according to the present invention comprises one or more separators by which the electrodes are mechanically separated.Suitable separators are polymer films, especially porous polymer films, that are unreactive towards metallic lithium.Particularly suitable materials for the separators are polyolefins, especially film-forming porous polyethylene and film-forming porous polypropylene.

[0097] A separator made of polyolefin, particularly polyethylene or polypropylene, may have a porosity in the range of 35 to 45%. A suitable pore size is, for example, in the range of 30 to 500 nm.

[0098] In another embodiment of the present invention, the separator can be selected from PET nonwoven fabrics filled with inorganic particles. Such separators can have a porosity in the range of 40-55%. Suitable pore sizes are, for example, in the range of 80-750 nm.

[0099] The battery according to the invention may further comprise a housing which may have any shape, for example a cube, or the shape of a cylindrical disk or can. In one variant, a metal foil configured as a pouch is used as the housing.

[0100] The battery according to the invention exhibits good cycling stability and low capacity loss.

[0101] The battery according to the present invention may comprise two or more electrochemical cells that are combined with each other, for example, connected in series or connected in parallel. A series connection is preferred. In the battery according to the present invention, at least one electrochemical cell contains at least one cathode according to the present invention. Preferably, in the electrochemical cell according to the present invention, the majority of the electrochemical cells contain the cathode according to the present invention. Even more preferably, in the battery according to the present invention, all the electrochemical cells contain the cathode according to the present invention.

[0102] The present invention further provides a method for using the battery according to the present invention in equipment, especially mobile equipment.Examples of mobile equipment are vehicles, such as automobiles, bicycles, aircraft, or water vehicles, such as boats or ships.Other examples of mobile equipment are manually operated, such as computers, especially laptops, phones, or powered hand tools, for example in the construction sector, especially drills, battery-powered drivers, or battery-powered staplers.

[0103] The present invention is further illustrated by the following examples. EXAMPLES

[0104] Show me how Li in aqueous solutions was measured by inductively coupled plasma optical emission spectroscopy (ICP-OES): Instrument: ICP-OES Agilent 5100 SVDV; Wavelength: Li 670.783 nm; Internal standard: Sc 361.383 nm; Dilution factor: Li; Calibration: external.

[0105] Elemental analysis of fluorine and fluoride was performed according to standardized methods (DIN EN 14582:2016-12 for sample preparation for total fluorine content determination (waste samples); detection method is ion-selective electrode measurement; DIN 38405-D4-2:1985-07 (water samples; digestion of inorganic solids followed by acid-supported distillation and fluoride determination with an ion-selective electrode)).

[0106] Starting materials: "Battery grade" LiOH·H2O (hereafter also referred to as "LiOH bg"), available from Livent, has a fluoride content of less than 5 ppm.

[0107] LiF is commercially available from Sigma Aldrich.

[0108] I. Providing starting materials for firing I.1 Synthesis of precursors, step (a.1) Deionized water was placed in a stirred tank reactor and thermostated at 45° C. The pH value was then adjusted to 11.3 by adding aqueous sodium hydroxide solution.

[0109] The coprecipitation reaction was started by simultaneously feeding aqueous solutions of transition metal sulfates and sodium hydroxide through a coaxial nozzle at a flow ratio of 1.9 with a total flow rate of 12 hours average residence time. The transition metal solution contained Ni and Mn in a molar ratio of 1:2 and a total transition metal concentration of 1.65 mol / kg. The aqueous sodium hydroxide solution was a 50% by weight solution of sodium hydroxide. The pH value was maintained at 11.3 by separately feeding aqueous sodium hydroxide. Starting from the start of all feeds, the mother liquor was continuously removed. After 29 hours, all feed flows were stopped. The resulting suspension was filtered, washed with distilled water, dried at 120°C in air and sieved to obtain the mixed transition metal (TM) oxyhydroxide precursor. The precursor TM-OH.1 was obtained with an average particle size (D50) of 6 μm.

[0110] I.2 Synthesis of LiOH containing LiF, step (b.1) ~1 tonne of mechanically treated battery scrap containing spent cathode active material containing nickel, cobalt and manganese, organic carbon in the form of graphite and soot, and residual electrolyte, as well as further impurities including inter alia fluorine compounds, phosphorus and calcium, was treated to obtain reduced material according to the process described in Jia Li et al., Journal of Hazardous Materials, 2016, 302, 97-104. The atmosphere in the torrefaction system was air, where oxygen reacts with the carbon in the battery scrap to form carbon monoxide, and the treatment temperature was 800°C.

[0111] After reaction and cooling to ambient temperature, the heat-treated material was recovered from the furnace and mechanically processed to obtain particulate material that was analyzed by powder X-ray diffraction, elemental analysis and particle size distribution.

[0112] The Li content is 3.6% by weight, which is the basis for the following leaching procedure (see below). The Fluorine (2.6% by weight) is mainly expressed as inorganic fluoride (2.3% by weight). The particle size is well below 1 mm, with a D50 of 17.36 μm.

[0113] Comparing the obtained XRD pattern with the calculated reference pattern for Ni (identical to one of CoxNi1-x (x=0-0.6), Co, Li2CO3 and LiAlO2), it can be concluded that Ni exists only as metallic phase, as pure Ni or as an alloy in combination with Co. The whole sample shows a typical ferromagnetic behavior when in contact with permanent magnet materials. As lithium salts, Li2CO3 and LiAlO2 are clearly identified by their characteristic diffraction patterns.

[0114] Leaching of heat-treated black material with Ca(OH)2: A PFA flask was charged with 30 g of the heat-treated battery scrap described above and 9 g of solid Ca(OH)2. The solids were mixed. 200 g of water was then added with stirring and the entire mixture was refluxed for 6 hours. After 6 hours, the solids were filtered and a filtrate sample was taken and analyzed for Li (c(Li)=0.49% by weight) and F (c(F)=0.015% by weight).

[0115] Solid LiOH from leached LiOH filtrate The filtrate from the above experiment was dried to obtain solid LiOH as monohydrate, which contained fluoride. To adjust the fluoride content, two different procedures were applied: (A) From 150 mL of filtrate containing 0.49 wt.% lithium and 0.015 wt.% fluoride, water was completely evaporated (40 °C, 42 mbar). LiOH·LiF.1 was obtained. XRD of LiOH·LiF.1 showed traces of Li2CO3 impurity. The latter was due to contact with air during most of the process steps. Next to carbon-based impurities, elemental analysis showed that fluoride was one of the main impurities (c(F) = 0.5 wt.%).

[0116] (B) 150 mL of filtrate from another LiOH leaching experiment, containing 0.49 wt.% lithium and 0.015 wt.% fluoride, was concentrated six-fold by evaporation (40 °C, 42 mbar), filtered, and finally dried under a nitrogen stream at 40 °C for 24 h. XRD of LiOH·LiF.2 showed traces of Li2CO3 impurity; the latter due to contact with air during most of the process steps. Next to carbon-based impurities, elemental analysis showed fluoride to be one of the main impurities (c(F) = 0.25 wt.%).

[0117] I.3 Synthesis of LiOH containing fluoride, step (b.2) CO2 was introduced (ambient conditions, ~5 L / h) for 7 h into a LiOH solution containing 2.6 wt% lithium and 0.017 wt% fluoride. A white solid immediately became visible. After 7 h, the solid was filtered, dried, and analyzed by X-ray diffraction and elemental analysis: Li2CO3·LiF.2 (Li = 19.0 wt%, F = 0.22 wt%). No separate LiF could be detected.

[0118] II. Preparation of Cathode Active Material II.1 Mixing process (c.1) and firing process (d.1) “Battery grade” LiOH·H2O (hereafter also referred to as “LiOH bg”), commercially available from Livent and containing less than 5 ppm fluoride, was used to mix with LiOH·LiF.1.

[0119] Step (c.1): The mixture of precursor TM-OH.1, LiOH bg and LiOH·LiF.1 was mixed three times for 1 min in a Kinematica MICROTRON laboratory mixer with a molar ratio of Li / (Ni+Mn) = 1.33:1. The mass ratio of LiOH·LiF.1 and LiOH bg was 1:1. A mixture was obtained.

[0120] Step (d.1): The mixture of step (c.1) was heated to 950°C at a heating rate of 3°C / min and held for 6 hours under forced flow of oxygen. After cooling to ambient temperature, the resulting powder was deagglomerated and sieved through a 32 μm mesh. CAM.1 was obtained. No accumulation of fluoride was detectable.

[0121] Electrochemical testing in coin half cells shows excellent first cycle discharge capacity and cycling stability.

[0122] II.2 Preparation of cathode active material CAM.2 “Battery grade” LiOH·H2O (hereafter also referred to as “LiOH bg”), commercially available from Livent and containing less than 5 ppm fluoride, was used to mix with LiOH·LiF.2.

[0123] Step (c.2): The precursors TM-OH.1 and LiOH·LiF.1 were mixed in a Kinematica MICROTRON laboratory mixer in a molar ratio of Li / (Ni+Mn) = 1.33:1 for 1 min three times.

[0124] Step (d.2): The mixture of step (c.2) was heated to 950°C at a heating rate of 3°C / min and held for 6 hours under forced flow of oxygen. After cooling to ambient temperature, the resulting powder was deagglomerated and sieved through a 32 μm mesh. CAM.2 was obtained. No accumulation of fluoride was detectable.

[0125] D50=12 μm measured by laser diffraction on a Malvern Instruments Mastersizer 3000 instrument. Li and transition metal contents were determined by ICP analysis. Residual moisture detected at 250 °C was below 300 ppm.

[0126] II.3 Preparation of comparative cathode active material C-CAM.3 Comparison process C-(b.3): bg of LiOH·H2O was mixed with LiF in a mass ratio of 99.66:0.34 (corresponding to CAM.1). As can be seen from the crystals, LiF crystals remain in the premix.

[0127] Step C-(c.3): The premix from precursors TM-OH.1 and C-(b.3) was mixed three times for 1 min in a Kinematica MICROTRON laboratory mixer with a molar ratio of Li / (Ni+Mn)=1.33:1. A mixture was obtained.

[0128] Step C-(d.3): Step (d.1) was repeated using the mixture obtained in step C-(c.3). After cooling to ambient temperature, the resulting powder was deagglomerated and sieved through a 32 μm mesh. C-CAM.3 was obtained. Some samples of C-CAM.3 showed different and unstable behavior compared to CAM.1 and CAM.2.

[0129] II.4 Preparation of Comparative Cathode Active Material C-CAM.4 Neither step (a) nor step (b) was performed.

[0130] Step C-(c.4): Precursor TM-OH.1 and LiOH·H2O bg were mixed three times for 1 min in a Kinematica MICROTRON laboratory mixer in a molar ratio of Li / (Ni+Mn) = 1.33:1. A mixture was obtained.

[0131] Step C-(d.4): Step (d.1) was repeated using the mixture obtained in step C-(c.4). After cooling to ambient temperature, the resulting powder was deagglomerated and sieved through a 32 μm mesh. C-CAM.4 was obtained.

[0132] III. Testing of Cathode Active Materials III.1 Cathode preparation, general procedure Cathode: PVDF binder (Solef® 5130) was dissolved in NMP (Merck) to make a 7.5 wt% solution. For electrode preparation, the binder solution (3 wt%) and carbon black (Super C65, 3 wt%) were suspended in NMP. After mixing using a planetary centrifugal mixer (ARE-250, Thinky Corp.; Japan), the CAM of the present invention or (comparative CAM) (94 wt%) was added and the suspension was mixed again to obtain a lump-free slurry. The solid content of the slurry was adjusted to 61%. The slurry was coated on Al foil using a KTF-S roll-to-roll coater (Mathis AG). All electrodes were calendered before use. The thickness of the cathode material was 100 μm, corresponding to 6.5 mg / cm2. All electrodes were dried at 105° C. for 7 h before cell assembly.

[0133] III.2 Preparation of electrolyte A base electrolyte composition containing 1M LiPF6 in a mass ratio of 3:7 with ethylene carbonate and ethyl methyl carbonate was prepared (EL Base 1).

[0134] III.3 Test cell construction Coin-shaped half-cells (20 mm in diameter, 3.2 mm in thickness) containing the cathode prepared as described in III.1 and lithium metal as the working and counter electrodes, respectively, were assembled and sealed in an Ar-filled glove box. Further, the cathode, anode, and separator were stacked in the order of cathode / separator / Li foil to fabricate half-coin cells. Then, 0.15 mL of EL base 1 was introduced into the coin cell.

[0135] IV. Evaluation of cell performance Evaluating the performance of coin half-cells The cell performance was evaluated using the manufactured coin type battery.

[0136] The initial performance and rate were measured as follows: The coin half-cell according to III.3 was tested in the voltage range of 4.3 V to 3.0 V at 25 °C. In the initial cycle, the cells were charged and discharged in CC-CV mode, i.e., a constant current (CC) of 0.1 C was applied until 4.3 V was reached during charging or 3.0 V was reached during discharging, respectively. After the initial formation cycle, the rate capability was measured at a constant discharge current of 3 C in CC mode.

[0137] The cycling performance and resistance increase were tested as follows: After initial performance evaluation, the coin cells were cycled 100 times at a constant charge current of 0.5 C and a constant discharge current of 1 C at 25° C. At the beginning of each discharge cycle, the resistance increase was measured by measuring the voltage drop after 30 seconds.

[0138] Batteries based on the cathode active materials of the present invention are superior. In particular, CAM.1 and CAM.2 show improved cycling stability and reduced resistance increase compared to C-CAM.3 and C-CAM.4. In particular, some samples of C-CAM.3 showed quite different electrochemical behavior. Without wishing to be bound by any theory, it is hypothesized that some samples of C-CAM.3 contain fluoride and others do not.

Claims

1. The following steps: (a) providing a particulate oxide or (oxy)hydroxide or carbonate of TM, the TM comprising nickel and manganese, at least 50 mol % of the TM being manganese, the particulate oxide or (oxy)hydroxide having an average particle size (D50) in the range of 1 to 16 μm; (b) providing a lithium source containing 0.01-2.5 wt. % fluoride, said fluoride being uniformly dispersed within said lithium source, said lithium source being selected from lithium hydroxide, lithium oxide and lithium carbonate; (c) mixing said oxide or (oxy)hydroxide or carbonate of TM with said fluoride-containing lithium source, optionally with an additional lithium source containing less fluoride, and optionally with one or more dopants based on at least one metal other than lithium; (d) heat treating the mixture resulting from step (c); 2. A method for making a fluoride-doped cathode active material, comprising:

2. TM is a compound represented by the general formula (I): (Ni a Co b Mr c ) 1-d M d (I) (wherein a is in the range of 0.2 to 0.5; b is 0 or in the range of 0.01 to 0.1; c is in the range of 0.5 to 0.8; d is in the range of 0 to 0.1; M is at least one of Al, Mg, Ti, Mo, Nb, Ta, W, and Zr; a + b + c = 1) The method of claim 1, wherein the metal combination is

3. 3. The method of claim 1 or 2, wherein the lithium source is selected from lithium hydroxide and lithium oxide.

4. The method according to any one of claims 1 to 3, wherein step (d) is carried out at a temperature in the range of 850 to 1150°C.

5. 5. The method according to any one of claims 1 to 4, wherein the mass ratio of the fluoride-containing lithium source to the fluoride-free lithium source is in the range of 1:1 to 1:

20.

6. The mixing step (c) comprises at least the following two substeps: (c1) mixing a fluoride-containing lithium source with a fluoride-free lithium source; and (c2) mixing the mixture resulting from substep (c1) with an oxide or (oxy)hydroxide or carbonate of said TM and, where applicable, with dopant(s); The method of any one of claims 1 to 5, comprising:

7. 7. The method of any one of claims 1 to 6, wherein the dopant(s) is selected from oxides and hydroxides of Al, Mg, and transition metals selected from Ti, Mo, Nb, Ta, W and Zr.

8. 8. The method according to any one of claims 1 to 7, wherein the lithium source with homogeneously dispersed fluoride is obtained by a recycling process of used batteries.

9. 9. The method of claim 1, wherein the fluoride is lithium fluoride.

10. 10. The method according to any one of claims 1 to 9, wherein the stoichiometry of lithium in step (c) is in the range of 90-95 mol% relative to the sum of TM and non-lithium metals from the dopant(s), if applicable, and step (d) is followed by another step of mixing with a lithium source and another heat treatment step.

11. 11. The method of any one of claims 1 to 10, wherein in the lithium source provided in step (b), no separate crystals or accumulations of fluoride are detectable by particle size distribution, X-ray diffraction and SEM / EDX.

12. General formula Li 1+x T.M. 1-x O 2-y F y and having an average particle size (D50) in the range of 1 to 16 μm, wherein TM comprises nickel and manganese, and at least 50 mol % of TM is manganese, x is in the range of 0.05 to 0.4, y is in the range of 0.0002 to 0.03, and F is uniformly distributed in the cathode active material and is not accumulated on the outer surfaces of secondary particles of the cathode active material.

13. TM is a compound represented by the general formula (I): (Ni a Co b Mr c ) 1-d M d (I) (wherein a is in the range of 0.2 to 0.5; b is 0 or in the range of 0.01 to 0.1; c is in the range of 0.5 to 0.8; d is in the range of 0 to 0.1; M is at least one of Al, Mg, Ti, Mo, Nb, Ta, W, and Zr; a + b + c = 1) The particulate cathode active material of claim 12 , wherein the metal combination is:

14. (A) at least one particulate cathode active material according to claim 12 or 13; (B) carbon in a conductive state; (C) Binder material a cathode comprising:

15. (1) At least one cathode according to claim 14; (2) at least one anode; and (3) at least one electrolyte A battery comprising:

Citation Information

Patent Citations

  • Particles, process for production thereof and use thereof

    US20130209840A1

  • Method of manufacturing lithium nickel complex oxide, lithium nickel complex oxide manufactured thereby, and cathode active material including the same

    US20150064563A1

  • Nonaqueous electrolyte secondary battery and method for manufacturing the same

    US5773168A